Trainee clinical psychologists' adaptation and professional functioning: A longitudinal study - Kuyken, W; Peters, E; Power, M; Lavender, T (2003)
Clinical psychology training is a professionally formative period, which provides an opportunity to enable trainees to learn good self-care skills and mature approaches to learning. If realized, this can support lifelong learning and high levels of professional functioning. This study sought to use transactional coping theory and experiential learning theory to improve our understanding of what factors predict changes in psychological adaptation and professional functioning over the course of clinical psychology training. A mixed prospective within-persons and cross-sectional between-persons design was used. A sample of 183 trainee clinical psychologists (60.2% response rate) from 15 British clinical psychology training programmes participated at time one, 167 of whom participated at time 2 a year later (91.3% of the time 1 sample). They completed measures of appraisal, coping, social support and professional functioning at times 1 and 2. Path analyses suggested that trainees who appraised the demands of training as manageable, and reported greater access to appropriate support, engaged in less avoidance coping, reported fewer problems of psychological adaptation and were more likely to approach the task of learning and working appropriately and resiliently. Implications for clinical psychology training are suggested. Copyright © 2003 John Wiley and Sons, Ltd.